(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Active reading is a learner-centered approach that transforms reading from a passive decoding activity into an interactive and reflective cognitive process. In contemporary education, especially in language learning, academic literacy, and lifelong learning contexts, active reading strategies are essential for developing deep comprehension, critical thinking, and independent learning skills. This article offers a comprehensive, original, and plagiarism-free discussion of active reading strategies. It examines theoretical foundations, practical techniques, educational benefits, and realworld applications, making it suitable for international newspapers and academic publications